India's water future to 2025-2050: business-as-usual scenario and deviations - Amarasinghe, Upali A.; Shah, Tushaar; Turral, Hugh; Anand, B.K. (International Water Management Institute, 2007)
With a rapidly expanding economy many changes are taking place in India today. The business-as-usual (BAU) scenario, which assumes the continuation of current trends of key water demand drivers, will meet the future food demand. However, it leads to a severe regional water crisis by 2050, where many river basins will reach closure, will be physically water-scarce and will have regions with severely overexploited groundwater resources. While the alternative scenarios of water demand show both optimistic and pessimistic water futures, the scenario with additional productivity growth is the most optimistic, with significant scope for reducing future water demand.